2022
DOI: 10.53685/jshmdc.v3i2.127
|View full text |Cite
|
Sign up to set email alerts
|

Parental Role in Recognition, Prevention and First Aid Management of Foreign Body Aspiration amongst Children

Abstract: Background: Foreign body aspiration (FBA) is a commonly observed, fatal but preventable condition in children. To reduce the incidence of FBA, it is essential to provide parents with knowledge and guidelines regarding the prevention and management of FBA. Objectives: To assess parental knowledge and parental role in the prevention and first aid management of foreign body aspiration in children. Methods: A descriptive cross-sectional study was carried out at Mayo Hospital, Lahore from January 2019 to September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Such findings indicate a lack of awareness among the adult population. Inadequate adult knowledge was reported in other studies conducted in KSA [ 38 , 39 ] and in other regions and countries such as Jordan, [ 40 ] Pakistan, [ 27 ] India, [ 22 ] Brazil, [ 14 ] and Japan. [ 41 ] On the contrary, a study conducted in Nigeria showed that there was good parental knowledge regarding FBA and 47.4% knew that they should not give groundnuts/seeds or small toys to children <3 years.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Such findings indicate a lack of awareness among the adult population. Inadequate adult knowledge was reported in other studies conducted in KSA [ 38 , 39 ] and in other regions and countries such as Jordan, [ 40 ] Pakistan, [ 27 ] India, [ 22 ] Brazil, [ 14 ] and Japan. [ 41 ] On the contrary, a study conducted in Nigeria showed that there was good parental knowledge regarding FBA and 47.4% knew that they should not give groundnuts/seeds or small toys to children <3 years.…”
Section: Discussionmentioning
confidence: 85%
“…Many accidental childhood deaths are caused by tracheobronchial FBA, which is a life-threatening emergency. [ 26 , 27 ] The present study investigated the community’s previous FBA experience and their knowledge regarding FBA.…”
Section: Discussionmentioning
confidence: 99%